ANALISIS BIBLIOMETRIK : MEDIA TERAKOTA DALAM ART THERAPY - Khaelani, Fawwas Firdaus; Khusumadewi, Ari; Purwoko, Budi; Winingsih, Evi (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry, 2024)
Abstract: This article aims to evaluate the development of research on terracotta media in art therapy through data searches in Dimensions and analysis using the Vosviewer application. The method used is descriptive Bibliometric analysis with a focus on Dimensions data processed through Vosviewer. The results showed that co-authorship (author collaboration) and co-occurrence (frequency of keyword occurrence) analysis using Vosviewer, based on metadata from 4,224 publications, indicated fluctuations in the number of terracotta media in art therapy research publications from 2015 to 2024. By utilizing the Vosviewer application for network visualization, overlay visualization, and density visualization, the main keywords in this study were identified, including treatment, art, effect, history, and stress. This research shows fluctuations, with the main focus on art therapy that serves to reduce stress and depression, studying theories related to human behavior, the application of art therapy treatments and functions, and the application of art therapy in a structured manner using technological developments. The decline in research interest in 2021 can be attributed to the shift in focus towards new technologies. The conclusion of this study is that the development of research on terracotta media in art therapy is still experiencing fluctuations, with a spike occurring before declining in 2021. In addition, themes related to terracotta media and art therapy are still not widely discussed.Abstrak: Artikel ini bertujuan untuk mengevaluasi perkembangan penelitian mengenai media terakota dalam art therapy melalui pencarian data di Dimensions dan analisis menggunakan aplikasi Vosviewer. Metode yang digunakan adalah analisis Bibliometrik deskriptif dengan fokus pada data Dimensions yang diproses melalui Vosviewer. Hasil penelitian menunjukkan bahwa analisis co-authorship (kolaborasi penulis) dan co-occurrence (frekuensi kemunculan kata kunci) menggunakan Vosviewer, berdasarkan metadata dari 4.224 publikasi, mengindikasikan adanya fluktuasi dalam jumlah publikasi penelitian media terakota dalam art therapy dari tahun 2015 hingga 2024. Dengan memanfaatkan aplikasi Vosviewer untuk visualisasi jaringan, visualisasi overlay, dan visualisasi densitas, teridentifikasi kata kunci utama dalam penelitian ini, termasuk treatment, art, effect, history, dan stress. Penelitian ini menunjukkan fluktuasi, dengan fokus utama pada art therapy yang berfungsi untuk menurunkan stres dan depresi, mempelajari teori yang berkaitan dengan perilaku manusia, penerapan treatment dan fungsi art therapy, dan pengaplikasian art therapy secara terstuktur dengan menggunakan perkembangan teknologi. Penurunan minat penelitian pada tahun 2021 dapat dikaitkan dengan pergeseran fokus menuju teknologi baru. Kesimpulan dari penelitian ini adalah bahwa perkembangan penelitian tentang media terakota dalam art therapy masih mengalami fluktuasi, dengan lonjakan terjadi sebelum menurun pada tahun 2021. Selain itu, tema-tema yang berkaitan dengan media terakota dan art therapy masih belum banyak diangkat.